Interference and Elimination of Fe3+ During Spectrophotometric Testing of Typical Pollutants in Coking Wastewater - Jiang, Fengcheng; Qiu, Yao; Wang, Mingshi; Zhao, Shuguang; Xu, Yahui; Xu, Manman; Zhang, Chuanbing (International Journal of Natural Resources and Environmental Studies, 2024)
As typical pollutants in coking wastewater, pyridine, indole, quinoline, and phenol have the advantages of rapidity and accuracy when determined in aqueous solution using UV spectrophotometry, but the presence of other substances in the water can interfere with the results. In this study, the spectrophotometric detection of pyridine, indole, quinoline, and phenol in coking wastewater was interfered with by Fe3+. To minimize this interference, hydroxylamine hydrochloride (HA) was selected as a masking agent to eliminate the interference of Fe3+ on the detection. The results indicated that spectrophotometric determination was significantly affected by Fe3+, and the level of interference increased with the concentration of Fe3+. HA can effectively reduce the absorbance of Fe3+ in the wavelength range of 250-350 nm. It exhibits a strong masking effect on the determination of Fe3+ in indole and phenol solutions, but it hampers the detection of pyridine and quinoline. HA has a better elimination effect on the interference of different concentrations of Fe3+, which can make the relative error of the determination results of indole and phenol less than 5% and 10%, respectively.